Jual Beli Followers Media Sosial TikTok Menurut Etika Bisnis Islam: Studi Kasus di UMKM Online Shop Fathcloth Desa Telukpinang - Fitriyah Fitriyah; Kholifatul Husna Asri (ALIF, 2022)
TikTok is a platform that is currently popular, especially during the Covid-19 pandemic. TikTok media sosial is a place to share varied content, be it videos, songs, dancing, singing and other things that require creativity. This research aims to increase knowledge and skills about the process of buying and selling followers on media sosial TikTok according to Islamic business ethics which is now widely known by the public. The research method used is a qualitative research approach that uses a natural setting with the intention of interpreting the phenomena that occur and is carried out by involving various existing methods. The population that will be used as research is sellers and buyers at Fathcloth MSME in Cibolang Village, Bogor Regency. The sample is one MSME owner and three of his employees as sellers followers and 10 buyers, each of whom has an online shop account and a personal account. The instruments used were direct observation and interviews with MSMEs selling followers. The results of this study are that in the implementation of sellers and buyers both know the interests of the followers who will be traded and there are no elements of fraud or against legal sources that already exist in the Koran and Sunnah, from various sources nas-nas The Qur'an and Hadith and the logic of fiqh rules that have been studied, the law of buying and selling followers on TikTok is permissible as long as it is not misused for fraudulent facilities and in accordance with Islamic business ethics, namely openness in buying and selling followers on TikTok media sosial in Cibolang Village, Bogor Regency.